Effect of doe–litter separation and photostimulation on reproductive performance of rabbit does - Eiben, Csilla; Sándor, Máté; Sándor, Ferenc; Mohaupt, Mónika; Kustos, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2019)
The reproductive performance of controlled nursing Hycole rabbits (n=1800) subjected to light stimulation (F) or doe–litter-separation plus light stimulation (DF) before AI (on day 11) instead of hormonal oestrus synchronization was compared with evaluating two reproduction cycles in spring in Galgamácsa and Kartal rabbit farms. At both farms on day 8 before AI the daily 9 h and 50 lux basal LED lighting was increased to 16 h and 100 lux light intensity that was gradually set back until day 5 after AI to basal lighting. The F rabbits nursed controlled until day 14 (from 9 a.m. to 10 a.m.) using metal-plate as separation. The DF rabbits also nursed controlled but they skipped the nursing on day 10 and so there was a 47–48 h doe–litter separation (DLS) prior to AI combined with light stimulation. The DF rabbits turned already on day of AI to free nursing. DLS with light stimulation seemed to improve reproduction but sexual receptivity, pregnancy and kindling rates of the DF and F does did not differ significantly in Galgamácsa (DF: 60, 90 and 89%; F: 59, 89 and 88%) nor in Kartal (DF: 61, 88 and 88%; F: 59, 87 and 86%). With DLS and light stimulation the number of born kits per litter increased (P<0.05) in Galgamácsa (DF: 13.3 and F: 12.9) but hardly changed in Kartal (DF: 11.5 and F: 11.3). Compared to the F rabbits the productivity (number of total born kits per 100 AI) of the DF rabbits was 3.8% better in Galgamácsa (1139 vs 1184) and 4.1% better in Kartal (1008 vs 968). Based on our results a 1–7% improvement in productivity can be expected with the use of DLS and photostimulation compared to the farm practice (only light stimulation) depending on the farm conditions and reproduction cycles.